The Development and Validation of a Cognitive Diversity Scale for Chinese Academic Research Teams - Dong, Feng; Peng, Jian; Wang, Xiao; Tang, Minhui (Frontiers in Psychology, 2021)
Cognitive diversity is an important concept stemming from western management research in the 1990s. With the rapid development of science and technology, there is a growing interest in the composition of an academic research team, such as team diversity. However, there is no tool available for measuring team cognitive diversity for academic research teams. Based on Van der Vegt’s theoretical model of Team Cognitive Diversity (TCD), an Academic Research Team Cognitive Diversity Scale (ATCDS) is developed and validated for an academic research team in our research with two studies (N = 737). In Study One, in-depth interviews and panel discussions were conducted to generate a preliminary questionnaire. In Study Two, the questionnaire was administered among academic research teams. Exploratory factor analysis (EFA) revealed four factors regarding cognitive diversity: 1) the way of thinking, 2) knowledge and skills, 3) the view of the world, and 4) beliefs about what is right and wrong. The factor structure was further validated by confirmatory factor analysis (CFA). Moreover, correlation and regression analyses showed that academic research team cognitive diversity was positively related to team creativity (r =.306, p <.01) and performance (r =.204, p <.10). To sum up, our newly developed 15-item ATCDS is sufficiently reliable and valid to be used for understanding cognitive diversity among academic research teams.